Preclinical Evaluation of Tropic Activity on Isolated Frog Heart by Using Volatile Oil of Nigella sativa Seeds - Samadder, Sanchita Subhendunath; Singh, Shristi; Saha, Anumita; Chatterjee, Aishi; Majumdar, Mrityunjoy; Roy, Sourav; Roy, Prodip (Journal for Research in Applied Sciences and Biotechnology, 2022)
The lifestyle of people has changed over the time. Before the revolution days, people suffered from various diseases and the availability of medicines were not available. Today’s life is busier. Healthcare system has improved a lot but at the same time the number of people getting affected by different sources is still on a rise. The number one cause of death worldwide is due to heart diseases. The death rates due to cardiovascular disease increased. In order to improve the health conditions, there is a continuous development of synthetic and herbal medicines. Recently, rise in the use of herbal medicines have due to its natural origins and less side effects. One of the emerging herbs is Nigella sativa described as the remedy of all diseases. The tropic activity of the extracted volatile oil from Nigella sativa is observed on the isolated frog’s heart. The heart was isolated from the frog and was treated with adrenaline and acetylcholine to study its activity respectively. The isolated heart was also treated with the volatile oil of Nigella sativa seeds which produced dose dependent bradycardia like situation followed by cardiac arrest.